Effect of wet clothing removal on skin temperature in subjects exposed to cold and wrapped in a vapor barrier: a human, randomized, crossover field study - Hagen, Linn Therese; Brattebø, Guttorm; Dipl-Math, Jörg Assmus; Wiggen, Øystein; Østerås, Øyvind; Mydske, Sigurd; Thomassen, Øyvind (BMC emergency medicine, 2024)
Prehospital care for cold-stressed and hypothermic patients focuses on effective insulation and rewarming. When encountering patients wearing wet clothing, rescuers can either remove the wet clothing before isolating the patient or isolate the patient using a vapor barrier. Wet clothing removal increases skin exposure but avoids the need to heat the wet clothing during rewarming. Leaving wet clothing on will avoid skin exposure but is likely to increase heat loss during rewarming. This study aimed to evaluate the effect of wet clothing removal compared to containing the moisture using a vapor barrier on skin temperature in a prehospital setting. This randomized crossover experimental field study was conducted in a snow cave in Hemsedal, Norway. After an initial cooling phase of 30 min while wearing wet clothes, the participants were subjected to one of two rewarming scenarios: (1) wet clothing removal and wrapping in a vapor barrier, insulating blankets, and windproof outer shell (dry group) or (2) wrapping in a vapor barrier, insulating blankets, and windproof outer shell (wet group). The mean skin temperature was the primary outcome whereas subjective scores for both thermal comfort and degree of shivering were secondary outcomes. Primary outcome data were analyzed using the analysis of covariance (ANCOVA). After an initial decrease in temperature during the exposure phase, the dry group had a higher mean skin temperature compared to the wet group after only 2 min. The skin-rewarming rate was highest in the initial rewarming stages for both groups, but increased in the dry group as compared to the wet group in the first 10 min. Return to baseline temperature occurred significantly faster in the dry group (mean 12.5 min [dry] vs. 28.1 min [wet]). No intergroup differences in the subjective thermal comfort or shivering were observed. Removal of wet clothing in combination with a vapor barrier increases skin rewarming rate compared to encasing the wet clothing in a vapor barrier, in mild cold and environments without wind. ClinicalTrials.gov ID NCT05996757, retrospectively registered 18/08/2023.